Dataset on maternal attitudes about child maltreatment in nine countries using a Q-sort methodology - Woudstra, Mi-lan; van Ginkel, Joost; Branger, Marjolein; Emmen, Rosanneke; Alink, Lenneke; Asanjarani, Faramarz; Carcamo, Rodrigo; Hsiao, Celia; Mels, Cindy; Selcuk, Bilge; Soares, Isabel; Wang, Lamei; et al. (My University, 2020)
Analyses of the present data are reported in the article "Crossing Boundaries: A Pilot Study of Maternal Attitudes about Child Maltreatment in Nine Countries"[8]. Data were collected during home visits using the Maltreatment Q-Sort (MQS). A total of 466 mothers from nine different countries gave their opinion about child maltreatment by sorting 90 cards with parenting behaviors taken from the literature that reflect four types of child maltreatment, into 9 evenly distributed stacks (with 10 cards each) from least to most harmful for the child. This data article provides an overview of the content of the 90 items, which type of maltreatment they reflect, and the source of the items. The percentage of mothers labelling each of the MQS items as maltreatment is also presented. In addition, instructions are included about the administration of the MQS as well as data-entry and analyses of Q-sort data, accompanied by example datasets and syntaxes. This can serve as a manual for researchers interested in using Q-sort data. (C) 2020 The Author(s). Published by Elsevier Inc.
Keywords: child maltreatment; attitudes; mothers; culture; q-sort